Impact of a Yogic Breathing Technique on the Well-Being of Healthcare Professionals During the COVID-19 Pandemic - Divya Kanchibhotla MSc; Bharathi Saisudha MBBS, MD; Somya Ramrakhyani MD, MPH; Darshan H Mehta MD, MPH (SAGE Publishing, 2021)
Background The COVID-19 pandemic has created unprecedented challenges for healthcare globally, the brunt of which has been borne by the health care providers (HCPs). These challenges are felt more keenly in India, as they stretch an insufficiently resourced healthcare system. The long hours, cross over of responsibilities, lack of resources to adequately care for patients, and concerns around safety of self and loves ones, have led to a spike in anxiety, depression, insomnia and other stress - related disorders in healthcare providers. Sudarshan Kriya Yoga (SKY) is a mind-body intervention that has been studied in multiple clinical populations. Prior to this study, there has been no exploration of the impact of SKY on healthcare providers, specifically the impact of a mind-body intervention like SKY on HCPs during a pandemic. Objective This study aims to investigate the impact of SKY on the well-being of HCPs during the COVID-19 pandemic. Methods We conducted a pilot feasibility study with a single arm pre-post design. SKY was taught to participants in a 4-day online breath and meditation workshop. We measured outcomes related to depression, anxiety, resilience, life satisfaction, and quality of sleep. Results Ninety-two subjects completed the study survey before and after the intervention. A significant reduction was observed in the levels of stress, anxiety and depression immediately after the program. In addition, the participants reported sig1nificant improvement in life satisfaction, resilience, and the quality of their sleep. Conclusion The results indicate that SKY breathing technique had a positive impact on the well-being of healthcare professionals during the pandemic. Participants experienced improved quality of sleep, enhanced satisfaction with life, and increased resilience after SKY. This pilot study provides important data for future multi-site randomized controlled trials to study the impact of yogic techniques on well-being of the HCPs.